Central European Vaccination Advisory Group (CEVAG) guidance statement on recommendations for 2009 pandemic influenza A(H1N1) vaccination - (:unkn) unknown (ELSEVIER SCI LTD, 2010)
The 2009 influenza A(H1N1) pandemic is markedly different from seasonal influenza with the disease affecting the younger population and a larger than expected number of severe or fatal cases has been seen in pregnant women, obese people and in people who were otherwise healthy. In Europe, influenza activity caused by the 2009 influenza A(H1N1) virus has passed the winter peak with nearly all countries now reporting lower influenza activity. However, although the rate of 2009 pandemic influenza A(H1N1) is declining, fatal cases continue to be reported and the future is hard to predict. The most effective protection against influenza is vaccination and increasing vaccine coverage is the only way to eliminate uncertainties regarding possible future waves of 2009 pandemic influenza A(H1N1). Recommendations have been developed for several central European countries but there is no clear or uniform definition with respect to priority groups or age groups who should receive vaccination. This paper contains the Central European Vaccination Advisory Group (CEVAG) guidance statement on recommendations for the vaccination of adults and children against 2009 pandemic influenza A(H1N1). CEVAG recommends vaccination of all health-care workers, pregnant women, children >= 6 months and <2 years of age and people with chronic medical conditions as a first priority. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: 2009 pandemic influenza A(H1N1); Vaccination recommendations; Central Europe